Measurement of the double-differential inclusive jet cross section in proton–proton collisions at s?=13TeVs=13TeV Measurement of the double-differential inclusive jet cross section in proton–proton collisions at s?=13TeVs=13TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Friedl, M.; et al. (My University, 2016)
A measurement of the double-differential inclusive jet cross section as a function of jet transverse momentum pT and absolute jet rapidity | y| is presented. The analysis is based on proton–proton collisions collected by the CMS experiment at the LHC at a centre-of-mass energy of 13TeV. The data samples correspond to integrated luminosities of 71 and 44pb-1 for | y| < 3 and 3.2 < | y| < 4.7 , respectively. Jets are reconstructed with the anti-kt clustering algorithm for two jet sizes, R, of 0.7 and 0.4, in a phase space region covering jet pT up to 2TeV and jet rapidity up to | y| = 4.7. Predictions of perturbative quantum chromodynamics at next-to-leading order precision, complemented with electroweak and nonperturbative corrections, are used to compute the absolute scale and the shape of the inclusive jet cross section. The cross section difference in R, when going to a smaller jet size of 0.4, is best described by Monte Carlo event generators with next-to-leading order predictions matched to parton showering, hadronisation, and multiparton interactions. In the phase space accessible with the new data, this measurement provides a first indication that jet physics is as well understood at s=13TeV as at smaller centre-of-mass energies. © 2016, CERN for the benefit of the CMS collaboration.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2016). Measurement of the double-differential inclusive jet cross section in proton–proton collisions at ?s = 13 TeV. European Physical Journal C, 76(8). doi:10.1140/epjc/s10052-016-4286-3